A Retrospective Analysis of Information Technology in Tourism Research - Vaibhav BHATT; Pramendra SINGH; Shreeansh MISHRA; Shivam BHARTIYA; Pankaj TYAGI (African Journal of Hospitality, Tourism and Leisure, 2024)
The tourism industry has experienced a profound evolution in recent years, largely due to the influence of information technology. The rapid advancement of information technology has revolutionized the tourism sector. This study gives an overview of the research in Information Technology and Tourism from 2014 to 2023. The aim is to identify the publication trends, conceptual structure, intellectual structure, and collaboration structure with the help of bibliographic analysis including descriptive, co-citation, co-word and collaboration analysis. Scopus database was used to obtain the data for the study. 203 research articles published between 2014 and 2023 were extracted from the Information Technology and Tourism (ITT) journal and the data was analysed using the biliometrix tool of the R software version 4.3.1 and VOSviewer. Information Technology and Tourism (ITT) is the first scientific interdisciplinary journal focusing on the nature and role of information technology within the context of tourism, travel and hospitality. The findings of the study indicate that research in Information Technology and Tourism has shown remarkable growth in terms of both publications and citations, with a pronounced emphasis on collaborative research. Keyword and co-word analysis highlighted the applications of technology in the tourism and hospitality sector.